AB0632 Efficacy of hydroxychloroquine therapy on whole salivary components in patients with primary sjogren's syndrome. (23rd January 2014) - Corvaglia, S.; Vukatana, G.; Ermini, L.; Versura, P.; Coslovi, C.; Campos, E.; Gavaruzzi, G.; Malavolta, N.
Abstract : Background: Primary Sjogren's syndrome (P-SS) is a systemic autoimmune inflammatory disorder characterized by lymphocytic infiltration of the exocrine glands, especially salivary and lachrymal glands, that became dysfunctional, leading to the clinical symptoms of dry eyes and dry mouth. Human saliva contains many informative proteins that can be used for the detection of disease. The mainstay of treatment for the sicca symptoms is local therapy, and that for the milder systemic symptoms is hydroxycloroquine(1). Objectives: To examine the efficacy of hydroxychloroquine therapy on whole salivary components in patients with P-SS. Methods: 14 patents fulfilling Vitali et al criteria(2) for P-SS (all women, mean age 55 yrs, range 42-67 yrs) and 14 matched control subjects were enrolled. The mean duration disease was 36 months. The patients were evaluated at beginning of hydroxychloroquine therapy (400mg/day) (T0) and after six months therapy(T1).Whole saliva samples were collected at T0 and T1 by using graduated micropipette, centrifuged and stored at -80°C until analysis. Salivary gland function in P-SS patients was estimated at T0 by sequential salivary gland scintigraphy using 185MBq (5mCi)99m Tc-pertechnetate injected intravenously. Chip-based analysis was performed with the Agilent 2100 Bioanalyzer system (Agilent, Waldbronn, Germany) associated with the Lab-Kit Agilent Protein P230. Saliva total protein content (TP), alpha-amylase (Swiss-Prot P04745), serum albumin (P02768), lysozyme (P61626), Ig alpha-1 and alpha-2 chain C region (IgA P01876 and P01877) were recognized and quantized in all samples. To evaluate salivary glands impairment, the semi quantitative scoring system proposed by Shizukuishi et al(3) (total scintigraphic score: 0 normal function -12 severe dysfunction) was applied. Data were statistically elaborated using the MedCalc and SPSS 13.0 software, applying descriptive analyse and using Wilcoxon's test for paired data and Spearman's correlation coefficient rho (significance p<0.05). Results: TP, alpha-amylase, serum albumin and IgA were shown to be increased in P-SS patients as compared to control subjects at T0 (data expressed as media±SD, mg/ml, respectively 2.01±1.44vs0.61±0.42; 0.64±0.66vs0.025±0.09; 1.79±3.6vs0.013±0.08; 0.07±0.04vs0.018±0.012; p always<0.05) while lysozyme was decreased (0.21±0.11vs1.48±0.56). A statistically significant shift of all salivary proteins toward normal values was observed after six months of treatment (TP 0.91±0.76, alpha-amylase 0.32±0.38, serum albumin 0.85±1.47, IgA 0.01±0.01, lysozyme 0.31±0.14; p always<0, 01). A linear correlation between total protein content and scintigraphic scoring was shown in P-SS at T0 (rho=0.4, P=0, 02). Conclusions: Although the small sample, in our preliminary study we obtain a qualitative improvement of whole saliva total protein content after six months of hydroxychloroquine treatment in patients with P-SS. References: Venables PJ Best Practice & Research Clinical Rheumatology 2006;20:791-07 Vitali C, Bomardieri S, Moutsopoulos HM et al Ann Rheum Dis 2002;61:554-58 Shizukuishi K et al Annals of Nuclear Medicine 2003;17:627-31 Disclosure of Interest: None Declared